2020
DOI: 10.1016/j.jcp.2020.109245
|View full text |Cite
|
Sign up to set email alerts
|

Can we find steady-state solutions to multiscale rarefied gas flows within dozens of iterations?

Abstract: One of the central problems in the study of rarefied gas dynamics is to find the steady-state solution of the Boltzmann equation quickly. When the Knudsen number is large, i.e. the system is highly rarefied, the conventional iteration scheme can lead to convergence within a few iterations. However, when the Knudsen number is small, i.e. the flow falls in the nearcontinuum regime, hundreds of thousands iterations are needed, and yet the "converged" solutions are prone to be contaminated by accumulated error and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 69 publications
0
63
0
Order By: Relevance
“…Solid lines represent the accurate results from the Shakhov model (44) solved by the discrete velocity method [69], that is, doubling the number of spatial and discrete velocity points gives the same results. Solid squares (experimental data) are collected from Ref.…”
Section: Sound Propagation Between the Transducer And Receivermentioning
confidence: 99%
See 1 more Smart Citation
“…Solid lines represent the accurate results from the Shakhov model (44) solved by the discrete velocity method [69], that is, doubling the number of spatial and discrete velocity points gives the same results. Solid squares (experimental data) are collected from Ref.…”
Section: Sound Propagation Between the Transducer And Receivermentioning
confidence: 99%
“…In the framework of Gauss-Hermite quadrature, adding more discrete velocity grids is not economic, as these grids will be distributed in the region |v 1 | > 3 where the VDF is zero! In the discrete velocity method, it has already shown that designing numerical quadrature that is more suitable for wall-bounded problems [2,48,68] will greatly increase the [69], while symbols are approximate solutions of the Shakhov model when the molecular velocity space v is discretized according to the Gauss-Hermite quadrature of order N accuracy while reduce the computational cost. This may hint that to derive more accurate moment equations with limited number of moments, more suitable basis functions rather than the Hermite polynomials should be used.…”
Section: Reason Of Slow Convergence Of Moment Systems For Highly Rarementioning
confidence: 99%
“…We study the flow induced by a hot microbeam in the transitional flow regime by UGKS and compare with the solutions with the R26 moment method [33] and the GSIS [6]. The numerical setup is the same as Zhu et al [20].…”
Section: Flow Induced By a Hot Microbeammentioning
confidence: 99%
“…For the last several decades, researchers has been trying to develop effective multiscale numerical schemes [4][5][6][7][8][9]. In 2010, Xu et al proposes the unified gas-kinetic scheme, which is the first genuine multiscale scheme being able to capture the viscous effect with cell size much larger than the kinetic scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation